2020
DOI: 10.35848/1347-4065/abcf08
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature annealing behavior of defects in Mg-ion-implanted GaN studied using MOS diodes and monoenergetic positron beam

Abstract: Mg ions were implanted into Si-doped (5 × 1017 cm–3) n-GaN at a dose of 1.5 × 1011 or 1.5 × 1012 cm–2. MOS diodes were used to characterize the implanted GaN after 300 °C annealing for 3 h and after additional 500 °C annealing for 3 min. Although capacitance–voltage (C–V) characteristics varied with the dosage, the effects of acceptor-like defects induced by ion implantation were observed in the C–V characteristics independently of dosage and annealing temperature. A defect level at approximately 0.25 eV below… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 62 publications
3
17
0
Order By: Relevance
“…Since the (S,W) value for Mg-implanted GaN with N-implantation was identical to that for N-implanted GaN (not shown), the same identification of the defect species can be done. This conclusion agrees with that obtained for Mg-implanted GaN with different implantation energies and implantation dosages [24][25][26]34 . After annealing at 1000 and 1100°C, the (S,W) shifted toward the right-hand side.…”
Section: Resultssupporting
confidence: 91%
“…Since the (S,W) value for Mg-implanted GaN with N-implantation was identical to that for N-implanted GaN (not shown), the same identification of the defect species can be done. This conclusion agrees with that obtained for Mg-implanted GaN with different implantation energies and implantation dosages [24][25][26]34 . After annealing at 1000 and 1100°C, the (S,W) shifted toward the right-hand side.…”
Section: Resultssupporting
confidence: 91%
“…A similar behavior for (S,W ) was reported for Mg-implanted GaN with low [Mg]. [40] For the annealed samples, almost all (S,W ) values are located on the line connecting the values for defect-free GaN and (V Ga V N ) 3 , suggesting that the major defect species trapping positrons is vacancy clusters such as (V Ga V N ) 3 . For the sample with [Mg] ¼ 10 17 cm À3 , however, the (S,W ) value tends to be 2 , and (V Ga V N ) 3 are shown as blue symbols.…”
Section: Annealing Behavior Of Vacancy-type Defects In Mg-implanted Gansupporting
confidence: 78%
“…For the as-implanted sample with [Mg] ¼ 10 17 cm À3 , the (S,W ) value locates on the line connecting the value for defect-free GaN and the measured values for the as-implanted samples with higher [Mg]s, suggesting that the concentration of V Ga -type defects in this sample is lower than the vacancy concentration causing the saturation of positron trapping for vacancies (≅10 19 cm À3[23] ). A similar behavior for (S,W ) was reported for Mg-implanted GaN with low [Mg] [40]. For the annealed samples, almost all (S,W ) values are located on the line connecting the values for defect-free GaN and (V Ga V N ) 3 , suggesting that the major defect species trapping positrons is vacancy clusters such as (V Ga V N ) 3 .…”
supporting
confidence: 78%
“…On the other hand, a positron annihilation spectroscopy study revealed that the main vacancy defects generated by Mg-ion implantation were divacancy (V Ga V N ) defects. [24][25][26] The defect level corresponding to Mg-ion-implantation-induced V Ga V N has been detected electrically at E C − 0.25 eV using MOS diodes, which are sensitive to the near-surface region of implanted GaN. 26,27) Furthermore, according to Ref.…”
Section: Introductionmentioning
confidence: 99%